Long-term performance and life cycle assessment of energy piles in three different climatic conditions. (February 2020) - Sutman, Melis; Speranza, Gianluca; Ferrari, Alessio; Larrey-Lassalle, Pyrène; Laloui, Lyesse
Abstract: The main purpose behind the use of energy piles is to enable the exploitation of geothermal energy for meeting the heating/cooling demands of buildings in an efficient and environment-friendly manner. However, the long-term performance of energy piles in different climatic conditions, along with their actual environmental impacts, has not been fully assessed. In this paper, the results of a finite element model taking into consideration the heating and cooling demands of a reference building, and the intermittent operation of a ground source heat pump, are revealed to examine the long-term performance of energy piles. Furthermore, a life cycle assessment model is implemented to compare the environmental performance of energy piles and a group of conventional piles. The environmental enhancement provided by the adoption of a ground source heat pump system is quantified with respect to a conventional heating and cooling system. The obtained results show that (i) the energy pile system can meet the majority of the heating/cooling demands, except during the peak demands, (ii) the geothermal operation results in temperature fluctuations within the energy piles and the soil, (iii) the use of energy piles results in a significant reduction in environmental impacts in the majority of the examined cases. Graphical abstract: Image 1 Highlights: Long-term performance of energy piles in different climatic conditions were analysed. GSHP system was successful in providing majority of space heating–cooling demands. Auxiliary heating–cooling systems were required during peak demand periods. Life cycle assessment analyses were performed on conventional and energy piles. Energy piles resulted in lower environmental impacts in most of the examined cases.